STRATEGIC ENVIRONMENTAL ASSESSMENT POLICY OF CIREBON COASTAL AREA FOR SUSTAINABLE DEVELOPMENT - Endang Sutrisno; Ria Apriani (Jurnal Dinamika Hukum, 2017)
Government policy relies on the balance of economic and environmental conservation activities to achieve sustainable development. In the perspective of legal studies, this study employs normative legal research and empirical legal research methods, particularly descriptive analysis and qualitative analysis method. Cirebon City does not have a Strategic Environmental Assessment regarding coastal development management policy due to lack of Human Resources, institutional and budgetary constraints. Conservation activities are required to maintain the diversity of aquatic biota through habitat rehabilitation as well as flora and fauna preservation. Therefore, potential excavation, potential zone arrangement and formulation concept of coastal zone and small islands management system are conducted through arranging Strategic Environmental Assessment. This is are crucial considering the current condition of Cirebon City’s Coast along 7 (seven) kilometers. Approximately 20% of the coast suffer severe damage. This damage occurs due to people’s behavior who cut down the mangrove trees for their daily needs.Keywords: Strategic Environmental Assessment, Conservation